Role of Gymnastics in the Army School of Physical Training - Griffiths, DE (The Royal College of Surgeons of England, 2006)
INTRODUCTION: As a result of a single spinal injury seen at Frimley Park Hospital, we reviewed the injuries recorded at the Army School of Physical Training since December 1996. PATIENTS AND METHODS: This was a retrospective review of all acute accidents and injuries recorded in the Accident Book since its inception. RESULTS: Over 75% of the injuries that were serious enough to result in soldiers having their training terminated were as a direct result of gymnastic events such as vaulting, trampolining and somersaults. These events were also responsible for most of the small number of career-threatening injuries. CONCLUSIONS: This raises questions about the inclusion of gymnastic events in course training programmes, especially when considering its relevance to army training in general.